KUALITAS PELAYANAN PUBLIK DI KANTOR KELURAHAN MEDOKAN AYU KECAMATAN RUNGKUT KOTA SURABAYA - Anggreini Nur Fitriyah; Lukman Arif (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This research aims to find out and analyze how much service quality influence on community satisfaction or dissatisfaction with public service at Medokan Ayu Village Office in Surabaya City. Public service improvement is one of the efforts that can improve the quality of service for the community. Subdistricts as lower level providers must be able to provide good service quality to the community. This study use a descriptive quantitative method with a frequency data table analysis dan a 5-point Likert scale. The indicators used are a combination of theories according to Levine and Kotler namely (1) Reliability, (2) Responsiveness, (3) Assurance, (4) Emphathy, (5) Tangible, (6) Responsibility, and (7) Accountability. Data collection techniques are carried out using questionnaires addressed to 100 respondents. The research results show that in general the quality of public service in Medokan Ayu Village Office, Surabaya City is already qualified but still there are several indicators that must be improved in order to be more optimal in service delivery. However, the public remains satisfied with the ministry provided.